Measuring Time, Valuing Temporality. Conceptual and Methodological Analysis of Time and Temporality Surveys in Chile [Midiendo el Tiempo, Valorando la Temporalidad. Análisis Conceptual y Metodológico de Encuestas Sobre Tiempo y Temporalidad en Chile] - Vera-Vera, C (UNIV CHILE, FAC CIENCIAS SOCIALES, DEPT ANTROPOLOGIA, 2021)
There are few instruments in Chile aimed specifically at measuring the time dimension of social life. This contrasts with the large amount of data on this dimension that is unknown to researchers and public policy makers because it is located in surveys with objectives other than the one mentioned. This article makes this data recognizable. Covering exhaustively the period 2000-20018, it does so based on a classification matrix, based on conceptual distinctions such as "time" and "temporality" or between "description" and "valuation". This analysis also takes a critical look at the absences and biases in these data. We conclude that the empirical information available in Chile on the time dimension has increased during the period considered; that most of the questions privilege the measurement of "time" over "temporality"; and that this information focuses on the description of the distribution and frequency of activities over time, rather than on their valuation. In dialogue with acceleration theory and systems theory, the article concludes by showing the relevance of broadening the semantic horizon of studies on the temporal dimension, taking them beyond the focus on the objectivist description of time. © 2021 Universidad de Chile. All rights reserved.